Design of Real Time Anemometer Based on Wind Speed and Direction - Triwahju Hardianto; Bambang Supeno; Dedy Kurnia Setiawan; Syamsul Arifin; Gunawan Gunawan; Ekky Wahyu A (Proceeding of the Electrical Engineering Computer Science and Informatics, 2015)
Data acquisition of wind speed and wind direction are needed to get the data potential of wind power. The aim of this research is to generate a device of wind speed and wind direction with the real time condition. With this device, we will obtain an analysis about the potential of wind power electrical generation around the Puger beach, Jember, Indonesia. In this study and discussion, the main part is made in three hardware that is to measure wind speed, wind direction and to show real time data. The device which is used to measure wind speed using hall effect sensor as a transducer. With using of the active magnet that spins will be created pwm that will be read by sensor to get the wind speed. As for the shows wind direction, we use a compass sensor CMPS 03 is a digital sensor that outputs in the form of digital bits so that be able to show wind direction from 0° to 360°. The magnitude of angle will be used in analyzing the direction of the wind. Then the real time clock (RTC) will be used to directly to determine the time and date of recording data.